Effect of plant based product on coronary atherosclerosis - A case report - Sritharan, G.; Anpuchelvi, S. (Wayamba University, 2018)
Coronary heart disease (CHD) is the most common form of heart disease. CHD can be prevented and even controlled. Extensive clinical and statistical studies have identified several factors that can increase the risk of the best way to keep the heart healthy. CHD. Such as age, sex, stress and fatty and oily foods. Controlling Siddha/Ayurvedic plant based medicines of Cholesterol QR, Immuno QR provides a magnificent solution. Although many ayurvedic plants have shown to help heart disease. A 55 years old male married attended the outdoor clinic presented with chest pain on exertion. He was advised by doctor to undergo a bypass surgery for blocked arteries. He is the smoker and drunker. Investigation shows abnormal blood reports, ECG & Echo. Cholesterol QR, Immuno QR are the Ayurvedic medicines product to be used for the above condition. This can be taken initially with allopathic medicines. But when the patient feel better after 30 days. Then reduced the allopathic drugs. Instruct the patient to avoid fatty. Oily foods and follow diet restriction. After 50 days, the intake of Cholesterol QR & Immuno QR reduced the chest pain and able to work without any discomfort. Then, Patient continued the full course of 150 days treatment. No symptoms at all.
Keywords: Ayurvedic plants; By-pass surgery; Cholesterol QR; Immuno QR